The strategic dimension of the use of communication technologies to support learning: the case of portuguese public higher education - Batista, João (2012)
This paper presents partial results from a research project about the use Portuguese Public Higher Education Institutions are doing of Communication Technologies to support education. The paper describes the project rationale and the methodology used. Some results are also presented concerning the strategic dimension of the use of Communication Technologies to support learning, and their respect to teachers and to staff with institutional responsibilities. Finally, some conclusions are also discussed.